Growing a Project-Based Translation Pedagogy: A Fractal Perspective - Kiraly, Don (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2012)
This article traces a fractal path through educational psychology and philosophy in an attempt to elucidate an arborescent perspective of complementary inter-disciplinary sources of inspiration for a project-based translation pedagogy. Starting with a social-constructivist, project-based approach proposed at the turn of the millennium, an attempt is made to paint a broader picture of the synergistic influences underlying an emerging “holistic-experiential” approach to translator education. Post modernism, enactive cognitive science, complexity theory, transformational educational theory and social-constructivist epistemology are some of the complementary roots that can be seen as potential sources of inspiration to nourish a learning-centered approach to developing translator expertise in institutional settings.